Fundos de investimento imobiliário no Brasil: as características que explicam o desempenho - Barreto, José Victor Souza (2016)
This work aims to help investors who chose to invest their resources in the real estate market with their investment decision based on endogenous characteristics easily identified in the prospect of Real Estate Investment Funds (FIIs). Those considered important by the literature were selected and then some models were built in order to test their influence on the return. Initially, a complete model was built, with all variables, which showed inconclusive results, since most variables were not significant. Then, a reduced model was proposed with the variables that really had some contribution for the return, thus obtaining relevant results. Through this, it was possible to observe that FIIs investing in real estate development, focusing on the residential market and with low management fees, generated higher returns to investors.